2017
DOI: 10.1007/s10895-017-2108-0
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical-Experimental Photophysical Investigations of the Solvent Effect on the Properties of Green- and Blue-Light-Emitting Quinoline Derivatives

Abstract: This paper describes the investigations on the solvatochromic effect and the photophysical properties of quinoline derivatives, compounds with potential applicability in optoelectronic devices. Using an experimental and theoretical approach, the effect of the solvent and the insertion of the phenyl, nitro, amino and dimethylamino group in the quinoline backbone were investigated. The use of Density Functional Theory (DFT) calculations provided the bases for the understanding of the energetic transitions observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…To examine the efficacy of InCl 3 extensive comparative studies with several catalytic systems have been investigated. Thus, several reactions were scrutinized in the presence of catalysts like InBr 3 , AlCl 3 , FeCl 3, Cu(OTf) 2, CuCl 2, CAN, I 2, TFA, p-TsOH and BF 3 OEt 3 , respectively ( Table 1, entries [11][12][13][14][15][16][17][18][19][20]. All the tested acids gaive lower yields than that of InCl 3 , however, in the case of Cu(OTf) 2 , a mixture of compounds are observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To examine the efficacy of InCl 3 extensive comparative studies with several catalytic systems have been investigated. Thus, several reactions were scrutinized in the presence of catalysts like InBr 3 , AlCl 3 , FeCl 3, Cu(OTf) 2, CuCl 2, CAN, I 2, TFA, p-TsOH and BF 3 OEt 3 , respectively ( Table 1, entries [11][12][13][14][15][16][17][18][19][20]. All the tested acids gaive lower yields than that of InCl 3 , however, in the case of Cu(OTf) 2 , a mixture of compounds are observed.…”
Section: Resultsmentioning
confidence: 99%
“…1). In addition to bioactivity, quinolines scaffolds also show luminescent properties with potential applications in organic solar cells (OSCs), organic light emitting diodes (OLEDs), biomolecular markers, molecular probes and switches [12][13][14]. Moreover, quinoline-based dyes such as ethyl red iodide and pinacyanol ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, DFT provides a range of functionals and amongst these, B3LYP has been found as a reliable functional for the determination of optical, electronic, as well as structural properties of small‐ to medium‐sized organic molecules . The results obtained, after benchmark tests based on experimental and theoretical data for various functionals, have shown that the results obtained with B3LYP are generally in good agreement with the corresponding experimental values …”
Section: Computational Detailsmentioning
confidence: 62%
“…[29] Introducing amino-and nitro-functionalities as donor and acceptor groups, respectively, the optical and photophysical response can be drastically altered, while keeping the fundamental molecular backbone. [30][31] Moreover, strong solvatochromic effects were observed for this class of compounds; [26,[32][33] and for some derivatives dual emission was observed. [34][35][36][37] The basicity of the chromophores can be tuned, so that large variations in the pH response of quinolines are observed.…”
Section: Introductionmentioning
confidence: 86%